A Correlational Study between Microstructural White Matter Properties and Macrostructural Gray Matter Volume Across Normal Ageing: Conjoint DTI and VBM Analysis. (October 2018) - Pareek, Vikas; Rallabandi, VP Subramanyam; Roy, Prasun K
We investigate the relationship between Gray matter's volume vis-a-vis White matter's integrity indices, such Axial diffusivity, Radial diffusivity, Mean diffusivity, and Fractional anisotropy, in individuals undergoing healthy aging. We investigated MRI scans of 177 adults across 20 to 85 years. We used Voxel-based morphometry, and FDT-FSL analysis for estimation of Gray matter volume and White matter's diffusion indices respectively. Across the life span, we observed an inter-relationship between the Gray matter and White matter, namely that both Axial diffusivity and Mean Diffusivity show strong correlation with Gray matter volume, along the aging process. Furthermore, across all ages the Fractional anisotropy and Mean diffusivity are found to be significantly reduced in females when compared to males, but there are no significant gender differences in Axial Diffusivity and Radial diffusivity. We conclude that for both genders across all ages, the Gray matter's Volume is strongly correlated with White matter's Axial Diffusivity and Mean Diffusivity, while being weakly correlated with Fractional Anisotropy. Our study clarifies the multi-scale relationship in brain tissue, by elucidating how the White matter's micro-structural parameters influences the Gray matter's macro-structural characteristics, during healthy aging across the life-span.